Tad - Davies, Benji (Harper, an imprint of HarperCollins Publishers, 2020)
"Meet Tad. She's the smallest tadpole in a big pond. And she's not frightened of Big Blub. Not. At. All. But when her tadbrothers and tadsisters start to get bigger and disappear, Tad worries that she'll be left all alone. All alone in the dark, with Big Blub. Growing up might take longer when you start at the bottom, but sometimes tiny hearts have the biggest dreams."--Inside front jacket.